Performance Evaluation of Lablab Genotypes across Various Locations of Ethiopia - Melkam Aleme (Advances in Agriculture)
This study was conducted evaluate the performance of Lablab genotypes across various locations of Ethiopia. Twelve accessions of L. purpureus obtained from ILRI Genebank and a check registered variety from Bako Agricultural Research Center were sown under a 3 × 13 factorial experiment in a randomized complete block design (RCBD) during the rainy season in 2020, across three locations, namely Tepi, Bechi, and Kite sites of South West Ethiopia. The data were collected on the establishment, days to different physiological stages, forage yields, soil properties, and other related parameters. The data were subjected to analysis of variance using the general linear model of SAS and mean comparison via list significance difference test. A significant difference (p≤0.01) was observed across locations for most of the studied agronomic traits. The highest average dry matter (DM) forage yield recorded for T6 (accession 11613), T8 (acc. 10953), T5 (acc. 14417), and T4 (accession 11612) was 10.3, 8.7, 6.8, and 7.4 t/ha-1, respectively. Dry matter forage yield was positively associated and regressed with plant height and leaf-to-stem ratio. Lablab accessions are well adapted to the ecology tested. Lablab could also be produced in these locations without any remarkable disease problems. It is recommended that five top forage producing accessions be advanced for the next step of yield evaluation in standard multilocation. This leads to recommending best lablab accessions to be registered for the Tepi area and other similar agroecologies. Furthermore, recommended varieties should be evaluated through animal performance through feeding trials. Refining the main agronomic practice such as time of sowing, application of fertilizer, harvesting time, identifying best food crop-lablab integration methods, and feeding strategies is also vital to address in the future.